Independence – the desire of the people, the President of support the country (Journal of actual problems of jurisprudence, 2018)
This article describes the main ideas concerning the form of government in the Republic of Kazakhstan. It is noted that the presidential form of government best reflects the hopes and aspirations of the Kazakh people.Key word: The Republic of Kazakhstan, President, form of government, presidential republic, the Constitution, the leader of the nation.